THE ROLE OF KNOWLEDGE SHARING IN MEDIATING ORGANIZATIONAL INNOVATIVENESS, CLIMATE, AND MOTIVATION TO LEARN ON LECTURERS' INNOVATIVE WORK BEHAVIOUR - Linda Wati; Irwan Muslim; Purbo Jadmiko; Elfitra Azliyanti; Rani Rani (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study aims to analyze the factors that influence the Innovative Work Behaviour (IWB) of lecturers at Private Universities (PTS) in West Sumatra. Organizational Innovativeness Climate (OIC) and Motivation to Learn (MTL) are identified as the main factors that drive innovation. Knowledge Sharing (KS) acts as a mediating variable in the relationship between the two factors and the innovative behaviour of lecturers.This study uses a quantitative method with the Structural Equation Modeling (SEM) approach. Data collection techniques through questionnaire surveys with Proportional Stratified Random Sampling techniques. The results show that OIC and MTL have a significant influence on IWB and KS. KS is proven to be a mediating variable on the influence of MTL on IWB. However, Knowledge Sharing does not mediate the influence of OIC on IWB. These findings are important for Private Universities in creating a more innovative and competitive academic environment. Increasing the culture of KS and MTL, innovation in teaching can improve the IWB of lecturers. The results of this study will help PTS in improving academic competitiveness